2013
DOI: 10.3109/21678421.2013.803576
|View full text |Cite
|
Sign up to set email alerts
|

Eye tracking communication devices in amyotrophic lateral sclerosis: Impact on disability and quality of life

Abstract: People with amyotrophic lateral sclerosis (PwALS) show progressive loss of voluntary muscle strength. In advanced disease, motor and phonatory impairments seriously hinder the patient's interpersonal communication. High-tech devices such as eye tracking communication devices (ETCDs) are used to aid communication in the later stages of ALS. We sought to evaluate the effect of ETCDs on patient disability, quality of life (QoL), and user satisfaction, in a group of 35 regular ETCD users in late-stage ALS with tet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
87
2
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(102 citation statements)
references
References 24 publications
4
87
2
4
Order By: Relevance
“…AAC use is associated with improved quality of life and mood in people with severe dysarthria / anarthria (Caligari, Godi, Guglielmetti, Franchignoni, & Nardone, 2013; Korner et al, 2013). Message (voice) banking allows people to record their own voice and play it back on speech devices.…”
Section: Symptom Management As Als Progresses: Medications and Assistmentioning
confidence: 99%
See 1 more Smart Citation
“…AAC use is associated with improved quality of life and mood in people with severe dysarthria / anarthria (Caligari, Godi, Guglielmetti, Franchignoni, & Nardone, 2013; Korner et al, 2013). Message (voice) banking allows people to record their own voice and play it back on speech devices.…”
Section: Symptom Management As Als Progresses: Medications and Assistmentioning
confidence: 99%
“…Message (voice) banking allows people to record their own voice and play it back on speech devices. These devices can be operated manually, by eye gaze (Caligari, et al, 2013; Spataro, Ciriacono, Manno, & La Bella, 2014), or by head movement tracking technology, allowing communication to occur even in the later stages of the disease (Caligari, et al, 2013). Even for patients who use AAC effectively, however, it important to develop personalized communication strategies with the caregivers such as a system for quickly confirming understanding or asking for help.…”
Section: Symptom Management As Als Progresses: Medications and Assistmentioning
confidence: 99%
“…As ETCSs enable users to communicate and control their environment, these devices also fall under the category of 'electronic aids to daily living'. 8 Although the impact of ETCSs has been investigated for several other neurological conditions, 6,[9][10][11] to the best of our knowledge no previous report has been published on the effects of using this technology in patients with SCI. In order to justify purchasing large quantities of ETCSs for our institution, evidence on the benefits of using such technology is required.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 For instance, the introduction of high-tech augmentative and alternative communication aid systems for individuals with late-stage amyotrophic lateral sclerosis has enhanced their ability to communicate markedly. 6,7 Briefly, augmentative and alternative communication devices allow individuals to compensate their reduced ability to talk, write or type. High-tech eye-tracking devices also fall under the umbrella of augmentative and alternative communication strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Survey studies of adults with amyotrophic lateral sclerosis (ALS), using gazebased AT have reported outcomes of improved quality of life (Hwang, Weng, Wang, Tsai, & Chang, 2014), satisfaction with gaze-based AT (Caligari, Godi, Guglielmetti, Franchignoni, & Nardone, 2013), and that gaze-based AT enhanced the performance of activities such as communication face-to-face, e-mail, and internet surfing (Ball et al, 2010;Caligari et al, 2013;Hwang et al, 2014;Spataro, Ciriacono, Manno, & La Bella, 2014).…”
Section: Gaze-based Assistive Technologymentioning
confidence: 99%